The effect of an ISBAR-based clinical supervision model during handover on clinical decision-making and self-efficacy of nursing internship students: a quasi-experimental study - Faezeh Gheisari; Sedigheh Farzi; Mohammad Javad Tarrahi; Tahere Momeni-Ghaleghasemi; Saba Farzi; Fateme Nazari; Reza Tajmir riahi (BMC Medical Education)
Abstract Background Nursing internship students often lack the necessary clinical decision-making skills, confidence, and experience due to limited competence. To ensure safe and high-quality care, nursing faculty must train graduates with the self-efficacy required to make effective decisions in complex, dynamic, and high-stress healthcare environments. The handover process involves the information that plays a critical role in clinical decision-making and care planning. One of the frameworks used in handover process is ISBAR (Identification, Situation, Background, Assessment, Recommendation). The clinical supervision model serves as an educational and supportive approach aimed at enhancing self-efficacy and skills, including the use of handover. Objective This study aimed to investigate the impact of an ISBAR-based Clinical Supervision Model (CSM) during handover on clinical decision-making and self-efficacy in nursing internship students. Method This quasi-experimental, two-group (pre-test and post-test) study was conducted in selected hospitals affiliated with Isfahan University of Medical Sciences, Iran, in 2024. Participants were selected through convenience sampling and then randomly allocated to either the intervention or control group. Data were collected using the ISBAR communication checklist, the Self-Efficacy in Clinical Performance (SECP) questionnaire, the Clinical Decision-Making questionnaire, and the Manchester Clinical Supervision Scale (MCSS). The clinical supervision model and routine supervision were administered over six sessions for the intervention and control groups, respectively. Data were analyzed using SPSS version 16. Independent t-tests and chi-square tests were used to assess baseline differences between groups. Paired t-tests evaluated within-group changes in clinical self-efficacy and clinical decision-making scores. ANCOVA was applied to compare ISBAR communication scores across six time points and post-intervention clinical self-efficacy and decision-making scores, controlling for pre-intervention values. Repeated measures ANOVA assessed within-group changes in mean ISBAR scores over time, while MANOVA examined multiple, interrelated ISBAR subscale scores. A significance level of p < 0.05 was set for all analyses. Results There were no significant differences in baseline characteristics between the intervention and control groups (p > 0.05). According to the within-group analysis, changes in the ISBAR communication scores over time were significant in both the intervention and control groups (p Time < 0.001), with a greater increase observed in the intervention group (p Intervention < 0.001). The intervention group demonstrated a significant improvement in clinical decision-making (p < 0.001) compared to the control group. Clinical self-efficacy showed significant improvement in both the control and intervention groups after the intervention (P < 0.05). However, between-group analysis showed that the increase was higher in the intervention group than in the control group (P < 0.001).) The mean score of the Manchester questionnaire in the intervention group in this study was 130.30, reflecting the high impact of implementing the clinical supervision model. Conclusion The findings revealed that the use of the clinical supervision model based on the ISBAR framework led to improvements in clinical self-efficacy and clinical decision-making, alongside the enhancement of handover skills in nursing internship students. Therefore, it is recommended that this model be utilized in the education of nursing students and newly graduated nurses to ensure safe and high-quality care.